(m-15)(m+9)=m-15

Simple and best practice solution for (m-15)(m+9)=m-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (m-15)(m+9)=m-15 equation:


Simplifying
(m + -15)(m + 9) = m + -15

Reorder the terms:
(-15 + m)(m + 9) = m + -15

Reorder the terms:
(-15 + m)(9 + m) = m + -15

Multiply (-15 + m) * (9 + m)
(-15(9 + m) + m(9 + m)) = m + -15
((9 * -15 + m * -15) + m(9 + m)) = m + -15
((-135 + -15m) + m(9 + m)) = m + -15
(-135 + -15m + (9 * m + m * m)) = m + -15
(-135 + -15m + (9m + m2)) = m + -15

Combine like terms: -15m + 9m = -6m
(-135 + -6m + m2) = m + -15

Reorder the terms:
-135 + -6m + m2 = -15 + m

Solving
-135 + -6m + m2 = -15 + m

Solving for variable 'm'.

Reorder the terms:
-135 + 15 + -6m + -1m + m2 = -15 + m + 15 + -1m

Combine like terms: -135 + 15 = -120
-120 + -6m + -1m + m2 = -15 + m + 15 + -1m

Combine like terms: -6m + -1m = -7m
-120 + -7m + m2 = -15 + m + 15 + -1m

Reorder the terms:
-120 + -7m + m2 = -15 + 15 + m + -1m

Combine like terms: -15 + 15 = 0
-120 + -7m + m2 = 0 + m + -1m
-120 + -7m + m2 = m + -1m

Combine like terms: m + -1m = 0
-120 + -7m + m2 = 0

Factor a trinomial.
(-8 + -1m)(15 + -1m) = 0

Subproblem 1

Set the factor '(-8 + -1m)' equal to zero and attempt to solve: Simplifying -8 + -1m = 0 Solving -8 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1m = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1m = 0 + 8 -1m = 0 + 8 Combine like terms: 0 + 8 = 8 -1m = 8 Divide each side by '-1'. m = -8 Simplifying m = -8

Subproblem 2

Set the factor '(15 + -1m)' equal to zero and attempt to solve: Simplifying 15 + -1m = 0 Solving 15 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1m = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -1m = 0 + -15 -1m = 0 + -15 Combine like terms: 0 + -15 = -15 -1m = -15 Divide each side by '-1'. m = 15 Simplifying m = 15

Solution

m = {-8, 15}

See similar equations:

| -(5+3p)-6p=-4(p+2)-7 | | (y-8)(y+2)=y-8 | | 0.4/a=0.32 | | 7x-8=3x-40 | | 3a+(a+b)=180 | | a+3a+(a+b)=180 | | 1.5(x-1)-1.5=2.5(x-3) | | -8(4n+8)-2(1-3n)=-n+8+n+4 | | -2+2(6)= | | -4r+8=32 | | -3p+3p=-6(5p+1)+6(3+7p) | | -4.8/-1.6 | | -5(6p+8)+6(p-7)= | | -7/8x=-21/32 | | 4q-3.3=2.4q+10.78 | | 7(2x+3)+8=-6(7x+4)+3x | | -2x+6x-3= | | (-4t+8)(4t+1)=0 | | -5X+6/5=9X+7/2 | | 3x-5y=19 | | 180-x=2x+12 | | 3(2x+3)=-2x+2 | | 7(x-12)-11=22x-275 | | 5(2x-5)-3(x+1)-18x= | | (n-4)(n+4)=n-4 | | 2x-5=55+7x | | -(3)/(y-5)=(-(8)/5y-25)+1 | | -6(x+4)+158=13+25 | | t(3t+27)=66 | | -4/6x=12/24 | | 4x+56=5432 | | 5+7x=-x+53 |

Equations solver categories